DOMINASI NEGARA SEBAGAI SUMBER KONFLIK AGRARIA DI INDONESIA - Yanis Maladi (Faculty of Law, Universitas Diponegoro, 2012)
Abstract Agrarian problems which stick out lately have their deep roots in the cause of that. Agrarian problems sinewy roots in a long time since colonial, new forced labor until this time are structural. The conflict parties were not among the people, but they against big business in collaboration with the authorities. The style of conquest through a double-edged knife: Repressive State Apparatuses and ideological State Apparatuses. Looking at structural roots of agrarian conflicts which were closely linked, it is necessary to make fundamental changes of national laws agrarian by revamping the unequal agrarian structure so that it becomes more socially equitable of Pancasila. Agrarian conflicts would be eliminated if the domain principle of verklaring not be revived. The principles and values ​​which became the agrarian conflict resolution were to respect the laws in that community and strengthening the rights of agrarian resources. Keywords: Repressive State Apparatuses, Ideological State Apparatuses, Verklaring Domain, Pancasila. Abstrak Persoalan agraria yang mencuat akhir-akhir ini, mempunyai akar kausa yang dalam.Persoalan agraria telah berurat dan berakar pada masa yang panjang sejak masa kolonial, orde baru dan hingga kini yang bersifat struktural. Pihak-pihak yang berkonflik bukansaja antara rakyat dan rakyat, tetapi juga antara rakyat melawan bisnis raksasa yang berkolaborasi dengan penguasa. Corak penaklukan dilakukan melalui pisau bermata dua: Represive State Apparatuses dan Ideological State Apparatuses. Melihat konflik agraria yang akar strukturalnya berkelindan tersebut, maka perlu melakukan perubahan mendasar terhadap hukum agraria nasional dengan melakukan perombakan struktur agraria yang timpang menjadi lebih berkeadilan social yang bernafaskan Pancasila. Konflik agraria akan bisa dieliminasi apabila asas domein verklaring tidak dihidupkan kembali. Prinsip dan nilai yang menjadi dasar penyelesaian konflik agraria adalah menghormati hukum-hukum yang hidup di masyarakat dan penguatan hak-hak masyarakat atas sumber-sumber agraria. Kata kunci: Represive State Apparatuses, Ideological State Apparatuses, Domein Verklaring, Pancasila.